2019
DOI: 10.1007/s10615-019-00730-2
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Social Isolation and Health: An Analysis of Parent–Adolescent Dyads from the Family Life, Activity, Sun, Health, and Eating Study

Abstract: We examined the relationship between social isolation and health among parents and their adolescent children. Data came from the 2014 Family Life, Activity, Sun, Health, and Eating Study (FLASHE), a cross-sectional internet study from the National Cancer Institute. Parents and their adolescent children (ages 12-17) completed surveys about demographics, physical activity, and diet; analyses include all dyads in which at least one member provided information for any of the analyzed variables (N = 1851). Actor Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…We also report a trend in decreasing weekly energy expenditure along with an increase in body weight during the peak-lockdown. With people staying indoors (in some cities and states), the closures of many local parks and recreation areas, and cancellations of gyms and organized sports activities, these findings are not surprising and supported by other studies [ 35 , 36 ]. Moreover, increasing PA can reduce cravings for high-calorie foods as well as mood [ 37 ].…”
Section: Discussionsupporting
confidence: 54%
“…We also report a trend in decreasing weekly energy expenditure along with an increase in body weight during the peak-lockdown. With people staying indoors (in some cities and states), the closures of many local parks and recreation areas, and cancellations of gyms and organized sports activities, these findings are not surprising and supported by other studies [ 35 , 36 ]. Moreover, increasing PA can reduce cravings for high-calorie foods as well as mood [ 37 ].…”
Section: Discussionsupporting
confidence: 54%
“…The influence of social isolation and unhealthy lifestyle choices within a family unit has also been studied. Thompson et al 22 found a significant correlation between social isolation and an unhealthier lifestyle in parents with adolescent children, which also negatively influenced lifestyle behaviors of their adolescent children. Robins et al 23 found higher levels of household PA to be associated with lower levels of social isolation in communitydwelling older adults.…”
Section: Commentarymentioning
confidence: 99%
“…The present article considers the results of previous academic studies to discuss the concepts of social isolation and loneliness, both as distinct and related aspects with multiple effects on physical and mental health. The term social isolation is often used to reflect objective structural factors, the level and frequency of one's social interactions (e.g., living alone), whereas the term loneliness is used to reflect subjective perceptions (Hwang et al, 2020;Thompson et al, 2020). Current studies typically examine overall social isolation (social isolation from family members, social isolation from friends, living alone, and having limited social participation) (Taylor, 2020).…”
Section: Social Isolation and Lonelinessmentioning
confidence: 99%
“…There is an urgent need to develop and implement more appropriate programms and interventions for prevention or treatment of the negative physical and psychological effects of the pandemic. Family-level interventions may prove efective for improving health and wellbeing for multiple members of a household (Thompson et al, 2020). In clinical, counselling and psychotherapeutical practice, relaxation, breathing and creative meditation centered on nature helps in activating coping mechanisms (Raban-Motounu, 2019;Vitalia, 2019).…”
Section: The Need For Complex and Holistic Health Strategiesmentioning
confidence: 99%